Microsoft Project Application in Optimizing Activities for Compiling Activity Programs at the Lapadde Village Office - Khaera Tunnisa; Rakhmadi Rahman; Alvian Tri Putra; Mar’atuttahirah; Rosmiati; Lukman Hakim; Januar Fahrisal; Akmal Baharuddin Syam (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Information and communication technology is necessary for every government and private agency. As one of the government agencies, Lapadde Village, Parepare City, requires knowledge and communication technology to compile activity programs. From these problems, Lapadde Village staff need a solution that can help in compiling a reasonable, timely, quality program of activities according to the budget that has been provided. The method used to solve this problem is MS Project Application Training. MS application. Project is one of the software that can be used to manage scheduling, budget, and resources in an activity plan. The training activities are carried out in several stages, namely, presentation of Project Management and MS Project materials, problem analysis according to the case studies determined by the participants, and MS Project implementation in case studies equipped with training modules. This training results in participants knowing the MS Project application, its features, and how to implement it in the activity program.